Development Of Instrument For Evaluating Website Usability Focusing On University Website - Nur Sakinah, Abd Aziz; Adzhar, Kamaludin (2015)
It is crucial to develop the instrument for evaluate website usability. It’s important to test the questionnaire instrument before using it to collect data in actual study. Recently, there are only a few studies that include an evaluation by experts, then a pre-test with focus group and pilot test with respondents in testing the instrument. The initial instrument for this study is 60 item questionnaires. After going through 3 stages, the final instrument has 45 items of the questionnaire. The questionnaire instrument has been tested in 3 stages to ensure the construct validity and give confidence to the researcher about the instrument before distribute it for actual study. It also investigated whether the respondents understood and responded to the questionnaire instrument. Thereby, reducing incomplete data and non-response to ensure face validity and reliability.